PENCIPTAAN VALUE INOVATION MELALUI BLUE OCEAN STRATEGY - LUKMAN, BUDI WIJAYA (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
Blue Ocean Strategy is a business strategy that creates a new market space and yet have competitors. Blue ocean is offering many exciting opportunities. Business competition strategy Blue Ocean strategy that makes the actors can create new market space, reach new market demand. When companies give customers (customer value) or the innovation value (value innovation) is often inversely proportional to the total cost advantage (lower total cost) because what happens is the increase of the price of the product because of the additional value innovation. However, the blue ocean strategy that does not happen. Innovation value can be combined with low-cost strategy. Blue Ocean Strategy challenges companies to break out of the red ocean where no competitors, so the competition becomes irrelevant. This will create a blue ocean in the event of a pioneer of the product produced, the value offered innovations that can truly satisfy customer value, which is not easily imitated by competitors.